Land Degradation: Land under Pressure - Nkonya, Ephraim M.; Koo, Jawoo; Marenya, Paswel; Licker, Rachel (International Food Policy Research Institute, 2012)
In 2011 two United Nations bodies adopted ambitious goals for halting land degradation and achieving sustainable development. These goals will be difficult, but not impossible, to meet. The evidence presented here suggests several avenues for achieving a world with no land degradation. First, efforts to promote sustainable land management need to improve local and national governance while also enhancing international cooperation. Second, instead of focusing solely on fertilizer subsidies, countries should use broader and more cost-effective incentives to encourage farmers to adopt integrated soil fertility management.